Malignant ectomesenchymoma of the nasal cavity - Patil, Channappa N; Cyriac, Sanju; Majhi, Urmila; Rajendranath, Rejiv; Sagar, T G (Indian Journal of Medical and Paediatric Oncology, 2011)
Malignant ectomesenchymomas are rare tumors. This tumor affects predominantly young children. Most common site is head and neck. A multi modality approach should be appropriate for this soft-tissue tumor. We present a 43 year old female with malignant ectomesenchymoma of the nasal cavity.
Keywords: Ectomesenchymoma; malignant; rhabdomyosarcoma